The allocation of the digital dividend in Austria - Arne Börnsen; Tim Braulke; Jörg Kruse; Michael Latzer (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2011)
The digital dividend is the amount of spectrum that is freed up by the switch over from analogue TV to digital terrestrial TV in the UHF band. Drawing from a research project (Braulke et al. 2010) commissioned by the Austrian regulator RTR, this article prioritizes, analyses and evaluates the options of use of the 790 - 862 MHz frequency band - the socalled 'upper digital dividend' in Austria. The underlying economic considerations are based on an analysis of the incremental value. The two main options are the use of the spectrum for digital television (DVB-T) and the use for mobile broadband (MBB). The economic analysis clearly shows that the use of the upper digital dividend for MBB would generate the highest economic value. The Austrian government has, based on this analysis, decided to assign the upper digital dividend for MBB use from 2012 onwards. An auction of the spectrum will take place in 2011.
urn:nbn:de:gbv:705-opus-27784
Keywords: L96; L98; L82; 330; Digital dividend; spectrum policy; Austria; digital TV; mobile broadband; Funktechnik; Telekommunikationsnetz; Digitaler Rundfunk; Mobilkommunikation; Breitbandkommunikation; Kosten-Nutzen-Analyse; Österreich